2022
DOI: 10.1155/2022/1927881
|View full text |Cite|
|
Sign up to set email alerts
|

Study of the Significance of Thromboelastography Changes in Patients with Dyslipidemia

Abstract: Purpose. To investigate the changes in thromboelastography (TEG) in patients with dyslipidemia to study its effect on the blood coagulation status. Methods. 131 patients hospitalized in Fujian Provincial Jinshan Hospital from January 2018 to December 2020 were selected, and 64 cases in the hyperlipidemia (HL) group and 67 cases in the non-HL group were set according to whether their blood lipids were abnormal. By measuring the changes of each parameter of TEG in patients, the relevant parameters R value, K val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…We find that the PLT is significantly difference between HBeAg (+) patients versus HBeAg (−) patients (121.6 vs. 140.81, p = 0.001, Table 1), and the high HBV DNA level group versus the low HBV DNA level group (129.84 vs. 142.87, p = 0.011, Table 1); however, the level of the PLT count is in a normal range, which does not convey useful information to identify the level of serum HBV DNA for clinicians. In previous studies, authors have reported that the level of PLT was correlated with the amount of inflammation [23,24]. A high HBV DNA level means that since the patient is in an inflammatory phase, their PLT level is lower than that of the low HBV DNA level.…”
Section: Discussionmentioning
confidence: 98%
“…We find that the PLT is significantly difference between HBeAg (+) patients versus HBeAg (−) patients (121.6 vs. 140.81, p = 0.001, Table 1), and the high HBV DNA level group versus the low HBV DNA level group (129.84 vs. 142.87, p = 0.011, Table 1); however, the level of the PLT count is in a normal range, which does not convey useful information to identify the level of serum HBV DNA for clinicians. In previous studies, authors have reported that the level of PLT was correlated with the amount of inflammation [23,24]. A high HBV DNA level means that since the patient is in an inflammatory phase, their PLT level is lower than that of the low HBV DNA level.…”
Section: Discussionmentioning
confidence: 98%
“… 65 , 66 Additionally, dyslipidemia also affects the body’s fibrinolytic and anticoagulant mechanisms, which increase the probability of thrombus formation and makes blood clot dissolution less effective. 67 Figure 1 summarize the pathway depicting association between CVD and diabetic dyslipidemia. Alterations in lifestyle are essential for minimizing CVD risk and rebalancing lipid profiles that includes adhering to a healthy diet with diminished cholesterol, processed carbohydrates and saturated trans fats maintaining the body weight.…”
Section: Dyslipidemia and Diabetesmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%